2015
DOI: 10.1016/j.molcatb.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformation of Astragalus sapogenins using Cunninghamella blakesleeana NRRL 1369 and Glomerella fusarioides ATCC 9552

Abstract: a b s t r a c tThe microbial transformation of Astragalus sp. derived sapogenins, namely cycloastragenol, astragenol and cyclocanthogenol, by Cunninghamella blakesleeana NRRL 1369 and Glomerella fusarioides ATCC 9552 were investigated. The unique enzyme system of both fungi resulted hydroxylation, cyclization, dehydrogenation and oxidation reactions. Structures of the new metabolites were elucidated by 1-D ( 1 H, 13 C, NOESY), 2-D NMR (DQF-COSY, HMBC, HMQC, NOESY) and HR-MS analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…The 1D NMR spectra of 11 and 13 were identical to those reported for 20­( R ),24­( S )-epoxy-3β,6α,12β,16β,25-pentahydroxylanost-9­(11)-ene and 20­( R ),24­( S )-epoxy-3β,6α,12α,16β,25-pentahydroxylanost-9­(11)-ene, respectively.…”
Section: Results and Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The 1D NMR spectra of 11 and 13 were identical to those reported for 20­( R ),24­( S )-epoxy-3β,6α,12β,16β,25-pentahydroxylanost-9­(11)-ene and 20­( R ),24­( S )-epoxy-3β,6α,12α,16β,25-pentahydroxylanost-9­(11)-ene, respectively.…”
Section: Results and Discussionsupporting
confidence: 68%
“…Compounds 15 and 16 , the 3,4- seco derivatives of astragenol, were isolated previously from the biotransformation of this compound with Glomerella fusarioides . Metabolite 17 was also identified as 20­( R ),24­( S )-epoxy-6α,16β,25-trihydroxy­lanost-9­(11)-en-3-one by comparing its NMR data with those previously reported in the literature…”
Section: Results and Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our previous studies revealed the biotransformation capacity of the filamentous fungi, viz. Cunninghamella blakesleeana and Glomerella fusarioides , toward triterpenoids. In this study, we demonstrated the potential of an endophytic fungus ( A. eureka ) as biocatalyst to transform the steroidal sapogenin neoruscogenin. As a result, 14 new metabolites were obtained, and their structures were elucidated.…”
Section: Resultsmentioning
confidence: 79%
“…bacteria. The two fungi mainly provided hydroxylated metabolites together with products formed by dehydrogenation, cyclization and oxidation of Baeyer-Villiger, leading to a ring cracking [35,37]. It is an important reason why the addition of Astragalus water extract achieved the highest crude triterpenoid content.…”
Section: Effect Of Concentrations Of Astragalus Water Extractsmentioning
confidence: 99%